Kitab Suci Dalam Komunitas Basis Gerejani (KBG) di Paroki Katedral Ruteng-Manggarai-Flores - Adam Satu (Jurnal Alternatif Wacana Ilmiah Interkultural, 2013)
Basic Christian Community(BCC) is a newwayofbeing Church. The fundamental self-understanding ofthe Basic Christian Communitybecomes clear from“being a community of Jesus" and the Community stands under the apostolic norm of discipleship ofJesus wich is to be realized again and again in new circumstances. The rearch of Fr.Adam shows clearly a realistic picture about the appreciation of the members in various Basic Christian Communities in the Cathedral Parish in Ruteng that The practice of Bible Sharing is a phenomenon that is still to be properly socialized due to the fact that Basic Christian Community is a new movement in the Church.There is for sure a gap between the appreciation and the reality of participation and involvement in the Basic Christian Communities. The do have the Bible at home and honor it in a special place but still they don't have yet a regular habit to read the bible.